Revision of Brazilian species of Aleochara Gravenhorst of the subgenus Aleochara (Coleoptera: Staphylinidae: Aleocharinae) - Caron, Edilson; Moussallem, Marcelo; Bortoluzzi, Sidnei (Zootaxa, 2019)
Adults and larvae of Aleochara are found in fly-infested habitats, where the larvae are ectoparasitoids of fly pupae. There are three subgenera recorded in Brazil. This study provides a taxonomic revision of Brazilian species of the subgenus Aleochara. As a result, we recognize seven species in Brazil, A. bonariensis Lynch, A. bugnioni Fauvel, A. lustrica Say, A. chrysorrhoa Erichson and three species described by Sharp: A. auricoma, A. mundana and A. prisca. Redescriptions and illustrations of the male and female genitalia are provided for all species. Nomenclatural changes: A. bugnioni is considered a new junior synonym of A. lateralis Erichson, and A. pseudochrysorrhoa Caron, Mise & Klimaszewski is a new junior synonymy of A. bonariensis. In addition, the type of A. verecunda Sharp, was not studied and the name is considered as species inquirenda, while A. curtula (Goeze) is not confirmed in Brazil and its Neotropical records is discussed. Finally, a key to species is provided and an updated checklist of the Brazilian species of Aleochara (Aleochara), including synonyms, is compiled.